Automating Salesforce Marketing Cloud : reap all the benefits of the SFMC platform and increase your productivity with the help of real-world examples - Gifford, Greg; Hanshaw, Jason (Packt Publishing, 2022)
Make the most of Salesforce Marketing Cloud through automation and increase your productivity on the platform without adding any extra resources Key Features Increase your knowledge of automation theory and the applications of SFMC Explore automation with SFMC and its capabilities beyond general usage Understand the automation features and integrations of SFMC to use the platform from outside the user interface (UI) for maximum efficiency Book Description Salesforce Marketing Cloud (SFMC) allows you to use multiple channels and tools to create a 1:1 marketing experience for your customers and subscribers. Through automation and helper tasks, you can greatly increase your productivity while also reducing the level of effort required in terms of volume and frequency. Automating Salesforce Marketing Cloud starts by discussing what automation is generally and then progresses to what automation is in SFMC. After that, you'll focus on how to perform automation inside of SFMC all the way to fully running processes and capabilities from an external service. Later chapters explore the benefits and capabilities of automation and having an automation mindset both within and outside of SFMC. Equipped with this knowledge and example code, you'll be prepared to maximize your SFMC efficiency. By the end of this Salesforce book, you'll have the skills you need to build automation both inside and outside of SFMC, along with the knowledge for using the platform optimally. What you will learn Understand automation to make the most of the SFMC platform Optimize ETL activities, data import integrations, data segmentations, email sends, and more Explore different ways to use scripting and API calls to increase Automation Studio efficiency Identify opportunities for automation with custom integrations and third-party solutions Optimize usage of SFMC by building on the core concepts of custom integrations and third-party tools Maximize utilization of employee skills and capabilities and reduce operational costs while increasing output Who this book is for This book is for Salesforce Marketing Cloud users who want to know how to make their day to day lives more efficient and get the most out of the tool by working smarter, not harder. A solid understanding of SFMC and basic knowledge of what automation is will help you get the most out of this book.